Finance Provisions Under the Individuals with Disabilities Education Act 1997 Amendments - Deborah Verstegen (Educational Considerations, 2000)
The 1997 Amendments to the Individuals with Disabilities Education Act (P. L. 105-17), signed into law by the President Clinton on June 4, 1997, make comprehensive changes to the IDEA.